Thermodynamics and structure of Neptunium(V) complexes with formate: spectroscopic and theoretical study - Maiwald, Martin M.; Dardenne, Kathy; Rothe, Jörg; Skerencak-Frech, Andrej; Panak, Petra (Inorganic chemistry, 2020)
The temperature and ionic strength dependences of the complex formation of NpO2+ with formate in aqueous solution are studied by absorption spectroscopy (Im = 0.5-4.0 mol kg-1, T = 20-85 °C, [Form-]total = 0-0.65 mol kg-1), extended X-ray absorption fine structure spectroscopy (EXAFS) and quantum chemical methods. The complex stoichiometry and the thermodynamic functions of the complexation reactions are determined by peak deconvolution of the absorption spectra and slope analyses. Besides the solvated NpO2+ ion, two NpO2+ formate species (NpO2(Form)n1-n; n = 1, 2) are identified. Application of the law of mass action yields the temperature dependent conditional stability constants log β′n(T) at a given ionic strength. These data are extrapolated to IUPAC reference state conditions (Im = 0) using the specific ion interaction theory (SIT). The results show, that log β01(20 °C) = 0.67 ± 0.04 decreases by approximately 0.1 logarithmic units with increasing temperature, log β02(20 °C) = 0.11 ± 0.11 increases by about 0.2 logarithmic units. The temperature dependence of the log β0n(T) values is modeled with the integrated Van’t Hoff equation yielding the standard reaction enthalpy ΔrH0 and entropy ΔrS0 of the complexation reactions. The results show that the formation of NpO2(Form) is exothermic (ΔrH01 = −2.8 ± 0.9 kJ mol-1) whereas the formation of NpO2(Form)2- is endothermic (ΔrH02 = 6.7 ± 4.1 kJ mol-1). Furthermore, the binary ion-ion interaction coefficients εT(i,k) of the formed complexes are determined in NaClO4 and NaCl media as a function of the temperature. The coordination mode of formate toward the metal ion is investigated by EXAFS spectroscopy and quantum chemical calculations. A coordination of the ligand via only one O atom of formate to the metal ion is identified.